Merari Code Culture That Has Stunting Impact for Early Children, Especially in Beroro Village - Ghofirly, M; Husen, Wan Ridwan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The phenomenon of early marriage in Indonesia tends to increase and is sometimes associated with culture, namely habits that occur in an area. This can be seen from the data that the average age of first marriage for women has decreased, while on the other hand the condition of early marriage can be said to be contrary to efforts to improve the quality of family life. The purpose of this study was to examine how culture influences women's chances of early marriage and how the phenomenon of early marriage differs between urban and rural areas. Multiple logistic regression was used in the data from the Indonesian Family Life Survey (IFLS) IV 2014. The results of the analysis show that the culture of the Sasak, Banjar, Minang and Balinese ethnic groups has a positive and significant effect, that is, the chances of girls marrying early are greater than those of other tribes and when it is associated Based on regional and religious conditions, it turns out that Bali-Java, Sumatra and Kalimantan are also positively significant in cities, while only Bali-Javanese are positive and significant in villages.